MODEL KESESUAIAN LAHAN TANAMAN BULO PATTUNG (DENDROCALAMUS ASPER) DAN ARAHAN KONSERVASI DI DAS HULU JENEBERANG KAB.GOWA - Zhiddiq, Sulaiman; Pertiwi, Nurlita (Pascasarjana Universitas Negeri Makassar, 2023)
Bamboo petung Makassar Bulo Pattung (Dendrocalamus Asper) in the Hulu Jeneberang watershed can be found in several villages such as, in Topidi, Jo'jo Batara, Panaikang, and Parangkeke in Tinggimoncong sub-district, in Lengkese hamlet Bawakaraeng, Raulo, Bangkeng Tabbing, Pattiro, Majannang , Bontopanno, Bilanrengi, in Parigi sub-district, Gowa district. Management of bulo pattung plants in the Hulu Jeneberang watershed. Bulo Pattung, which has typical highland bambuo plants, occupies ideal land in terrain with elevations above 1,000 meters above sea level, which is very necessary to reduce the threat of surface erosion and landslides. This research aims to 1) Assess the suitability of the Bulo Pattung land in the Hulu Jeneberang watershed based on physical environmental parameters; 2) Make conservation directions for the Bulo Pattung plant. Determination of land suitability based on unit maps, which are derived from maps: land use, slope, soil, land form. Soil sampling, in land units. Physical environmental parameters include; temperature, water availability, rooting media, nutrient retention, salinity, toxicity, available nutrients, ease of processing, and terrain, field parameters taken when taking soil samples. Soil sample analysis is tested in the laboratory. Next, the suitability analysis is carried out. The results of the research show: 1) There is land suitability for conservation, namely S1 (Very Suitable), 2) Directions for land conservation based on land suitability derived from factors that limit land suitability, are recommended in land units with cliffs and steep slopes.